2019
DOI: 10.18632/oncotarget.27182
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L secretion by host and neoplastic cells potentiates invasion

Abstract: The presence of macrophages within breast tumors correlates with metastatic potential. These tumor-associated macrophages often take on a pro-tumorigenic (M2-like) phenotype resulting in the secretion of growth factors and proteases, including the lysosomal protease cathepsin L. Since cathepsin L also is frequently secreted by breast cancer cells and contributes to tumor invasion, metastasis, and angiogenesis, we hypothesized that secretion of cathepsin L by both tumor-associated macrophages and neoplastic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Soluble/secreted EpCAM (EpEX) is a 242 amino acid (aa) fragment lacking the signal peptide (23 aa), transmembrane domain (23 aa), and cytoplasmic tail (26 aa) [ 13 ]. CTSL, while typically expressed in the endosome, has also been shown to be secreted by tumor cells and potentiates invasion in multiple cancer types [ 37 , 38 ]. A study of congenital tufting enteropathy patients demonstrated that some EpCAM germline mutations can alter cellular trafficking and localization of EpCAM protein to the cell surface [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soluble/secreted EpCAM (EpEX) is a 242 amino acid (aa) fragment lacking the signal peptide (23 aa), transmembrane domain (23 aa), and cytoplasmic tail (26 aa) [ 13 ]. CTSL, while typically expressed in the endosome, has also been shown to be secreted by tumor cells and potentiates invasion in multiple cancer types [ 37 , 38 ]. A study of congenital tufting enteropathy patients demonstrated that some EpCAM germline mutations can alter cellular trafficking and localization of EpCAM protein to the cell surface [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Including cathepsins, other proteases such as urokinase-type plasminogen activator (uPA), tissue plasminogen activator (tPA), elastases, and matrix metalloproteinases (MMPs) form a cascade of proteolytic activation to facilitate degradation of extracellular matrix [282]. In models of breast cancer, TAM-derived cathepsin B [283], X [283], and L [284] were requisite for tumor cell invasion and metastasis. Likewise, cathepsin B [280], S [280], and X [191] from TAMs contributed to tumor cell invasion in pancreatic cancer.…”
Section: Role Of Cathepsins In Function Of Tamsmentioning
confidence: 99%
“…Likewise, cathepsin B [280], S [280], and X [191] from TAMs contributed to tumor cell invasion in pancreatic cancer. IL-4 has been repeatedly accused of stimulating cathepsin secretion in TAMs [254,280,284]. Besides secreted cathepsins, cathepsins in lysosomes of TAMs could be responsible for the digestion of internalized collagen fragment from tumor microenvironment [285].…”
Section: Role Of Cathepsins In Function Of Tamsmentioning
confidence: 99%
“…Further studies revealed that STAT3 and STAT6 promote cathepsin secretion by macrophages [56]. Recently, a study showed that inhibition of cathepsin L secretion by TAMs and breast cancer cells impairs invasion and M2-like TAM infiltration in the tumor microenvironment [57]. The macrophage inflammatory proteins 1α (MIP-1α or CCL3) and -β (MIP-1β or CCL4) are chemokines of the CC superfamily derived from immune cells, including macrophages.…”
Section: Tams In Cancer Cell Invasionmentioning
confidence: 99%